2007
DOI: 10.1007/s10295-007-0235-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification, cloning, and characterization of a multicomponent biphenyl dioxygenase from Sphingobium yanoikuyae B1

Abstract: Sphingobium yanoikuyae B1 utilizes both polycyclic aromatic hydrocarbons (biphenyl, naphthalene, and phenanthrene) and monocyclic aromatic hydrocarbons (toluene, m- and p-xylene) as its sole source of carbon and energy for growth. The majority of the genes for these intertwined monocyclic and polycyclic aromatic pathways are grouped together on a 39 kb fragment of chromosomal DNA. However, this gene cluster is missing several genes encoding essential enzymatic steps in the aromatic degradation pathway, most no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 42 publications
0
24
0
Order By: Relevance
“…These multiple dioxygenase systems are encoded by the XylXY, BphA1a2a, BphA1b2b, BphA1c2c, BphA1d2d, BphA1e2e, and BphA1f2f genes (Gibson and Parales, 2000;Kim and Zylstra, 1999;Ní Chadhain et al, 2007;Yu et al, 2007;Zylstra and Kim, 1997). This suggests that the reductase and ferredoxin components can serve as electron transport systems for multiple dioxygenases, e.g., naphthalene and biphenyl dioxygenases (Moritz et al, 2004).…”
Section: Catabolically Versatile Enzymes Used In Multiple Pahdegradatmentioning
confidence: 97%
“…These multiple dioxygenase systems are encoded by the XylXY, BphA1a2a, BphA1b2b, BphA1c2c, BphA1d2d, BphA1e2e, and BphA1f2f genes (Gibson and Parales, 2000;Kim and Zylstra, 1999;Ní Chadhain et al, 2007;Yu et al, 2007;Zylstra and Kim, 1997). This suggests that the reductase and ferredoxin components can serve as electron transport systems for multiple dioxygenases, e.g., naphthalene and biphenyl dioxygenases (Moritz et al, 2004).…”
Section: Catabolically Versatile Enzymes Used In Multiple Pahdegradatmentioning
confidence: 97%
“…Isolates able to degrade m-xylene include members of the α Proteobacteria (genus Sphingobium) (Chadhain et al 2007;Kim and Zylstra 1999), β Proteobacteria (genera Alcaligenes and Ralstonia) (Cavalca et al 2000;Olsen et al 1994), γ Proteobacteria (genera Pseudomonas and Pseudoxanthomonas) (Assinder and Williams 1990;DiLecce et al 1997;Duetz et al 1997;Jeong et al 2006;Kim et al 2008;Velazquez et al 2005Velazquez et al , 2006Williams and Worsey 1976;Worsey and Williams 1975), as well as members of the Actinobacteria (genus Rhodococcus) (Jung and Park 2004;Lee and Cho 2008). Isolates linked to m-xylene degradation from a contaminated site were primarily γ Proteobacteria (Pseudomonas or Stenotrophomonas species) (Hendrickx et al 2006), whereas clone library analysis revealed that a culture consuming m-xylene was dominated by a β Proteobacteria (Delftia acidovorans), with minor members of the community including species of the Proteobacteria (Khomenkov et al 2005).…”
Section: Relevant Genera Characteristics Of Identified M-xylene Degramentioning
confidence: 99%
“…To date, microbial ecologists have tended to focus on specific functional activities of key microbial groups, yet interconnectivities between microbial populations clearly have a significant influence on ecosystem function, necessitating a more global community‐based view of functional processes. The responses of in situ microbial communities to the presence of PAHs has been examined using techniques including clone libraries, molecular fingerprinting, stable isotope probing and qPCR of specific degradatory genes (Cheung and Kinkle, 2005; Leys et al ., 2005; Park and Crowley, 2006; Chadhain et al ., 2007; Grant et al ., 2007; Muckian et al ., 2007; Singleton et al ., 2009; Jones et al ., 2011). Many of these approachesrequire prior knowledge of gene sequences, which have been identified from pure culture studies, restricting our view of the extent of potential community function.…”
Section: Introductionmentioning
confidence: 99%